ANALISIS SITUASI DAN KONDISI FASILITAS KESEHATAN MITRA BPJS KESEHATAN SETELAH ENAM TAHUN IMPLEMENTASI JAMINAN KESEHATAN NASIONAL - Suryawati, Chriswardani (Jurnal Manajemen Kesehatan Indonesia, 2024)
In the sixth year, the implementation of JKN has resulted in achievements, especially community access to treatment at health facilities, but there are still many problems, especially in hospitals. This research is an observational study with qualitative methods. The informants are two government hospital directors and three private hospital directors, a triangulation of BPJSK officials. Hospitals have adaptively made adjustments, especially regarding the increase in the number of BPJSK participating patients, preparation of facilities and facilities, socialization of JPSBK regulations, and improvement of services to maintain the quality of services and to increase BPJSK patient satisfaction. Medical staff workload has increased but has yet to be accompanied by increased medical incentives, restrictions on medical authority, especially in administering drugs according to the BPJSK formulary and limiting medical support services and patient care days. This was all done to control costs due to reduced hospital income due to Ina-CBG payments from BPJSK. Hospitals must be innovative and creative in managing finances and generating revenue. The problem of late payments (claim pending) needs to be resolved immediately. Likewise, the satisfaction of internal hospital staff needs to be considered.